Pengembangan Bahan Ajar Buku Cerita Rakyat Bergambar Berbasis Aplikasi Canva Untuk Meningkatkan Hasil Belajar Peserta Didik Kelas IV Sekolah Dasar - Eni Setiyawati Setiyawati; Abdul Muktadir; Bambang Parmadie (UNIB Press, 2022)
The purpose of this study was to develop, determine user responses and determine the effectiveness of teaching materials for illustrated folklore books based on the Canva application in improving student learning outcomes. The type of research used is development research. The research model used is the ADDIE model. The type of data used is quantitative and qualitative data using instruments in the form of interviews, questionnaires, and questions. Based on the results of the study, it was concluded that the teaching materials that had been developed were suitable to be used as teaching materials in class IV Indonesian language content for finding characters in fiction stories. The percentage of expert validation results is 82% from material and language expert validation, and 91% from design expert validation. The user's response is very good because the results of the fourth-grade teacher questionnaire analysis show the percentage of the attractiveness aspect is 94%, the material aspect is 75%, the language aspect is 88% and the story selection aspect is 94%. Meanwhile, for the responses from students, the attractiveness aspect is 83%, the material aspect is 86%, the language aspect is 82% and the story selection aspect is 82%. The teaching materials developed were effective in improving the learning outcomes of fourth-grade students at SD Negeri 111 Bengkulu Utara. This is based on the results of the t-test with = 2.1 > = 2.0 then H0 is rejected and Ha is accepted.